Parotid Gland Abscess: A Series of Three Cases - Makrami, Ali Mohammed; Ahmed, Shihab Abdelmunim Osman; Bajonaid, Amal M.; Hezam, Asma Ali; surgery, Resident oral and maxillofacial (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Suppurative or secondary parotitis is an acute inflammatory infection of the parotidgland. It is also referred to as ascending parotitis because the pathogenesis issuggested to be an ascending bacterial infection through Stensen’s duct.(1,2)It differsfrom mumps in several aspects: 1- It is not contagious; 2- It frequently suppurates,and give rise to parotid abscess.(1)Symptoms of parotid gland abscess include: swelling at the angle of the mandiblewhich is usually accompanied by erythema of the overlying skin, trismus, shootingpain at the area of the parotid gland, fever, lethargy, and occasional dysphagia.(1) Themost common pathogen associated with acute bacterial parotitis is Staphylococcusaureus.(3) Some predisposing conditions and factors include: dehydration,malnutrition, poor oral hygiene, xerostomia, ductal obstruction, and some chronicdiseases such as diabetes mellitus.(4) Among the various imaging techniquesultrasonography is considered the first line for the evaluation of parotid abscess.(2) Ifleft untreated it might be complicated by deep neck space infection and sepsis.(5)Management includes hydration and administration of parenteral antimicrobialagent.(6) In case of abscess formation, surgical drainage is required.(6)